If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(x-5)+3=15
We simplify the equation to the form, which is simple to understand
-2(x-5)+3=15
Reorder the terms in parentheses
+(-2x+10)+3=15
Remove unnecessary parentheses
-2x+10+3=+15
We move all terms containing x to the left and all other terms to the right.
-2x=+15-10-3
We simplify left and right side of the equation.
-2x=+2
We divide both sides of the equation by -2 to get x.
x=-1
| (x+5)3=36 | | 5(2l+4)=50 | | 9x^2-y^2+4=0 | | (U+5)*8=80 | | 2(a-3)=38 | | (u-6)8=24 | | 3+7t-4t+2-6= | | 0.6x+0.40(100-x)=50 | | (q-9)2=16 | | 4w^2-24w-7=0 | | (e+4)3=27 | | 3x^4=67 | | A+2b-8b= | | (Q-7)*5=25 | | -8q+18q+-13q=9 | | 2b+5j=8.43 | | 5x+101=13x-11 | | (e+5)*6=54 | | Y-5=3x-6 | | 4k^2+16k-48=0 | | 6(x+1)=2x+57 | | E+5*6=54 | | Y=.5x-150 | | -11n=-132 | | 3(2x+3)-2(4x-3)= | | x-15.5=14.85-x | | x^2-49x+380=0 | | x+15.5=x+14.85 | | -3x-5+1+10=8+7x+8 | | 102(t+1)=102 | | 8m-3=11 | | 10h=5 |